EXPLORING EFFICACY OF KETAMINE COMBINATIONS: META ANALYSIS & REVIEW OF ITS USE IN SEDATION PROCEDURE - Yudha Ferriansyah; Bakti Setiadi (Universitas Airlangga, 2024)
Background Recently, there has been a shift in the philosophy regarding procedural sedation. The best sedation agent should have quick induction and recovery times with few side effects. Several studies have investigated the combination of Ketamine-Dexmedetomidine and Ketamine-Propofol for reducing potential negative side effects during sedation procedures. Methods The literature search was performed in PubMed, Medline, Cochrane and Google Scholar. Meta-analysis based on the PRISMA methods. All variables and data were pooled in Excel, SPSS version 26 and Cochrane. Results Total of 372 patients were in Ketamine-Dexmedetomidine group and 373 patients were in Ketamine- Propofol group. Patient characteristics in this study had a mean age of 2.4 to 9.1±1.6 years and mean weight 12 to 23.6±6 kg in the pediatric population and 27 to 51±8.5 years and 75 to 84.5±4.2 kg in the adult population. ASA criteria for each patient are ASA I-IV and the most ASA criteria in patients is ASA II. The procedure time from 5.7 to 63.4 ± 5.3 minutes and also comorbidities. Conclusion The combination of drugs in sedation procedures is the best choice to achieve a balanced effect in reducing negative side effects of drugs. Dexmedetomidine-Ketamine appears to be superior than Propofol- Ketamine in terms of hemodynamic stability, oxygen saturation and fewer adverse events. Eventhough Dexmedetomidine-Ketamine has longer recovery time and lower heart rate.